War of resolutions: Parliamentary blockades in the Kosovo negotiations - Dušan Reljić (Stiftung Wissenschaft und Politik (SWP), 2005)
The approaching start of the future status negotiations for Kosovo is marked by a hardening of positions in Pristina and Belgrade, as well as mounting violence in Kosovo itself. At the same time, differences are arising between the United States, which leans toward independence for Kosovo, and Russia and China, which oppose secession.(SWP Comments / SWP)
Keywords: 320